The Effect of NPWP Ownership Obligations, Tax Audits and Tax Collection on Tax Revenue - Raden Ai Lutfi; Rananda Septanta; Chaeru Syahru Ramdhani; Adi Sofyana Latif (Journal of Social Science, 2023)
Stand up comedy Indonesia is a talent search event held by Kompas TV. This type of verbal humor is more dominant than nonverbal. The language used in humor is different from the language used in serious communication. This study aims to analyze the humorous discourse in stand up comedy "Beni Siregar" on youtube. This research is a research with a qualitative descriptive approach, and discourse analysis method. The theory used is Wilson's theory of humor in (Emy 2015) which is the theory of liberation, conflict and misalignment. The data of this study is a recording of the stand up comedy "Beni Siregar" on youtube. The results showed that the conflict that views humor as a contradiction, misalignment in the speech of the stand up comedy "Beni Siregar" on YouTube media is true. The liberation of seeing humor in an emotional light is not found. The stand up comedy "Beni Siregar" is an entertaining comedy.